Rethinking Slum Planning: A Comparative Study of Slum Upgrading Projects - Istifada Alhidayatus Sibyan (The Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
The stigma slums have of being an urban problem is influenced by theoretical and empirical knowledge. This article reports a comparative study on the failure and success of slum upgrading projects in the Gecekondu slum area in Ankara, Turkey and the Semanggi slum area in Surakarta, Indonesia. In both cases there were different orientations and approaches in planning influenced by the perspective on slums. Related to the result of the study, this article offers at least three key perspectives to understand slums in the context of urban planning. Slum upgrading projects are not always about space formalization, physical improvement, or economic enhancement. Slum upgrading projects are also about community empowerment and social transformation contributing to urban development. The success of a slum upgrading project depends on the approach and perspective toward these urban issues within the local context. Different methods and focuses could result in different outcomes of the project. As such, those differences should be taken into account in the planning process.Abstrak. Stigma permukiman kumuh sebagai masalah perkotaan dapat dipengaruhi oleh pengetahuan yang bersumber dari teori dan pengetahuan empiris. Artikel ini adalah studi komparatif yang mencoba menggambarkan kegagalan dan keberhasilan proyek peningkatan permukiman kumuh dalam kasus daerah kumuh Gecekondu di Ankara, Turki dan daerah kumuh Semanggi di Surakarta, Indonesia. Hasilnya menunjukkan bahwa ada berbagai orientasi dan pendekatan dalam perencanaan. Perbedaan-perbedaan ini dipengaruhi oleh perspektif terhadap kumuh dalam perencanaan. Terkait dengan hasilnya, artikel ini menawarkan setidaknya tiga perspektif kunci untuk memahami daerah kumuh dalam konteks perencanaan kota. Proyek peningkatan permukiman kumuh tidak selalu tentang formalisasi ruang, peningkatan fisik atau peningkatan ekonomi. Selain itu, proyek perbaikan permukiman kumuh adalah tentang pemberdayaan masyarakat dan transformasi sosial yang berkontribusi terhadap pembangunan perkotaan. Keberhasilan proyek peningkatan permukiman kumuh tergantung pada pendekatan dan perspektif konteks lokal terhadap masalah perkotaan ini. Berbagai metode dan fokus dapat menghasilkan berbagai hasil proyek. Dengan demikian, perbedaan-perbedaan tersebut harus diperhitungkan dalam proses perencanaan.Kata kunci. Perspektif, perencanaan, pendekatan perencanaan, orientasi perencanaan, daerah kumuh.